Patient Satisfaction with Home care Service in Riau Province - Syafrisar Meri Agritubella; Yoza Misra Fatmi; Raja Sakhnan (JURNAL PROTEKSI KESEHATAN, 2022)
Home care service are an alternative treatment option that is used and is currently developing because it can reduce treatment costs and help families and patients continue to receive care while at home. The purpose of this study was to determine patient satisfaction with home care services in Riau Province. The research method used is descriptive by describing the satisfaction of patients who receive home care sampling. The sampling technique used accidental sampling which was taken after receiving hom care treatment, so that a total sample of 67 people was obtained. Data collection using a Satisfaction Questionnaire developed by Parasuraman. The results showed that 88,1% of respondents rated the home care service as satisfied. Suggestions for future research can develop an application to monitor the health status of post-treatment patients so that they can monitor patients at any time.